Long term effect of nutrition on thyroid disease - Hussein, Mohammed Salah; Asiri, Lama Samir; Asali, Sadeem Wadia; Alawlaqi, Abdulaziz Mohsin; Sibah, Gadeer Sameer; Alshammari, Bader Hadi; Gaban, Saltanh Mohammed; Almansory, Alanood Nawaf; AlGhamdi, Hind Mousa; Msallati, Jinan Hikmat; Al Dhaif, Hassan Mohammed; Rayshan, Ali Salem Al (International Journal Of Community Medicine And Public Health, 2021)
Many forms of thyroid diseases have been classified under autoimmune thyroid disease. These include hyperthyroidism or commonly known as Grave’s disease, and hypothyroidism commonly identified as Hashimoto’s thyroiditis. Many nutritional elements have been linked to the function of the thyroid gland as any disturbance in these elements can lead to the development of relevant thyroid diseases. The most important elements include iodine, iron, selenium, zinc, and soy. In this current manuscript, we aimed to discuss the effect of these nutritional elements on the development of thyroid diseases by reviewing relevant studies in the literature. Although it is widely known that iodine is an essential component for the synthesis and release of these hormones, exaggerated intake of iodine can also lead to the development of hypothyroidism by negative feedback mechanisms. Besides, it can also trigger abnormal autoimmune reactions which can lead to the development of AITD. Selenium is another important factor and evidence shows that it has been associated with Grave’s thyroiditis, however, further evidence is needed as recommended by previous investigations. Clinicians should also take care of iron, zinc, and soy levels during management to obtain a better prognosis.